The effects of cadmium on some growth parameters, physiology and genotoxicity of barley (hordeum vulgare l.) - SÜNER, SALİM; ÖZYİĞİT, İBRAHİM İLKER (My University, 2022)
Nowadays, rapid population growth has become critical in the world by causing many problems such as environmental pollution, global climate change, unplanned urbanization, and unhealthy living conditions. Environmental pollution is one of the most important problems and heavy metals, which are important raw materials for socio-economic development in the industry as a mineral resource cause mostly this pollution in recent years. All organisms that are exposed to heavy metals accumulate them from the air, soil, and fresh or underground water sources. One of the heavy metals that harmful for the environment and living things is cadmium (Cd) known to be toxic even at low concentrations.Therefore, in this study, different concentrations of Cd (0 for control, 50, 100, 200, and 400 μM for experimental groups) were applied to barley (Hordeum vulgare L. var. alta) plants, and some growth, development, physiological and genotoxic parameters were measuredcompared to the control group that is not exposed to Cd stress. The seeds used in the study were obtained from the Kyrgyzstan State Plant Genetic Resources Center and germinated in the plant climate room. ISSR molecular marker technique was used to determine the genotoxic effects of Cd in barley plants. In addition, the accumulation of Cd and some selected mineral nutrients in plants was measured by usinganinductively coupled plasma optical emission spectroscopy (ICP-OES) device. Furthermore, the amount of total chlorophyll was evaluated using the CCM-200plus Chlorophyll Content Meter. The cadmium accumulation values (as μg kg-1 ) in the control and experimental groups were measured as 34, 282, 410, 1178, and 1427 in the root; 14, 155, 323, 572, and 917 in the stem; 21, 118, 224, 595 and 1034 in the leaves respectively. Accordingly, the accumulation was in the form of root>leaf>stem. B, Ca, Fe, Mg, Mn, Ni, and Zn concentrations in the root, stem, and leaves of H. vulgare L. var. alta plants decreased inversely with increasing Cd concentration compared to the control group. While the total chlorophyll values decreased in all concentrations of Cd compared to the control, they showed some fluctuations within themselves. ISSR primers gave distinguishable and acceptable DNA band profiles on agarose gel were UBC 835, UBC 841, and UBC 842. According to the DNA band profiles in this study; increasing concentrations of Cd application changedthe intensity of the bands in all concentrationsby increasing or decreasingand it also,causednew band formations or disappearances in existing bands especially at 200 and 400 μM Cd applications.This shows that the plant makes an effort to cope with stress to a certain level and is successful, but is insufficient if it is above a certain degree of stress (especially in 200 and 400 μM Cd applications)
Keywords: Temel Bilimler; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary